Film "Mendadak dangdut" (2006); Pemahaman geografi budaya dan identitas - Kristianto, Bayu (Wacana, Journal of the Humanities of Indonesia, 2009)
Place has certain connotations that are involved in shaping the identity of an individual or a community. Due to the importance of place or location in identity formation, Cultural Studies has its own area of analysis focusing on the understanding of place, which is cultural geography. Peter Jackson (1989: 23, quoted by Giles and Middleton 1999: 104) defines cultural geography as a study on how cultures are constituted by social practises occurring in certain contexts which are influenced by historical and geographical factors. The discussion of artistic works centred on the role of place in identity formation becomes an interesting analysis. This research focuses on Rudi Soejarwo's film Mendadak Dangdut ('Suddenly Dangdut'). The film's setting is a densely populated district in Jakarta. As the plot centres around this setting, an analysis of how place influences the identity formation of the film's main character becomes significant. The research is made using approaches in cultural geography, along with two key concepts in Cultural Studies, which are identity and representation. It is aimed at finding a new consciousness as to how urban context, especially that related to an understanding of place, takes part in the formation of identity of individuals and communities.